"Comparison of structure and properties of nitrile rubber 40 H and 3604 by hot polymerization" - XU Bina, ZHANG Hai-yib, FAN Yong-jiangc, LI Dong-hongc, CUI Guo-fenga, LIU Qianga, GAO Wei-guangc (Hecheng xiangjiao gongye)
Molecule structure and glass transition temperature of raw rubber of the new nitrile rubber (NBR) 40 H by hot polymerization, and Mooney viscosity and curing characteristics of the compound, as well as thermal-oxidative aging resistance and oil resistance of the vulcanizates, were studied and compared with the traditional hot polymerized product NBR 3604. The results showed that the molecule structure of NBR 40 H was not significantly different from that of NBR 3604, both had similar glass transition temperatures and processing properties, and the mechanical property retention rates after thermal-oxidative aging and immersed in standard refe-rence oil were also similar. NBR 40 H could replace NBR 3604.